Using telehealth consultations for healthcare provision to patients from non-Indigenous racial/ethnic minorities: a systematic review. (12th February 2022) - Truong, Mandy; Yeganeh, Ladan; Cook, Olivia; Crawford, Kimberley; Wong, Pauline; Allen, Jacqueline
Abstract: Objective: The COVID-19 pandemic has seen a rapid adoption of telehealth consultations, potentially creating new barriers to healthcare access for racial/ethnic minorities. This systematic review explored the use of telehealth consultations for people from racial/ethnic minority populations in relation to health outcomes, access to care, implementation facilitators and barriers, and satisfaction with care. Materials and Methods: This review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis and the Joanna Briggs Institute Manual for Evidence Synthesis. Five major databases were searched to identify relevant studies. Screening, full-text review, quality appraisal, and data extraction were all completed independently and in duplicate. A convergent integrated approach to data synthesis was applied with findings reported narratively. Results: A total of 28 studies met the inclusion criteria. Telehealth-delivered interventions were mostly effective for the treatment/management of physical and mental health conditions including depression, diabetes, and hypertension. In several studies, telehealth improved access to care by providing financial and time benefits to patients. Technological difficulties were the main barriers to effective telehealth consultation, although overall satisfaction with telehealth-delivered care was high. Discussion: Telehealth-delivered care for racial/ethnic minorities offers promise across a range of conditions and outcomes, particularly when delivered in the patient's preferred language. However, telehealth may be problematic for some due to cost and limited digital and health literacy. Conclusion: The development and implementation of guidelines, policies, and practices in relation to telehealth consultations for racial/ethnic minorities should consider the barriers and facilitators identified in this review to ensure existing health disparities are not exacerbated.